Disfunction of Recognition and Subsidiarity: Usage of Dana Desa - Puspitasari, Condrodewi; Tyas, B Hari Saptaning; Winarti, Safitri Endah; Raharjo, Triyanto Purnomo (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
This study aims to determine the dysfunction of the village recognition and subsidiarity principles, particularly in Kalurahan Sumbermulyo, Bambanglipuro, Bantul, due to the annual issuance of the Permendes PDTT regarding the priority of using Dana Desa and the increasing intervention through Presidential Regulation Number 104 of 2021, specifically Article 5 paragraph (4). This research employed descriptive qualitative methods with an interpretive approach. The results showed fluctuations in the use of Dana Desa. From 2015 to 2018, Dana Desa were solely used for infrastructure development. Starting in 2019, in addition to infrastructure development, Dana Desa were also utilized for community empowerment. In 2020, due to the Covid-19 pandemic, village funds were refocused on pandemic response efforts. In 2021, Dana Desa were used to accelerate the achievement of the SDGs Desa. In 2022, the use of Dana Desa experienced significant intervention through Presidential Regulation Number 104 of 2021. In practice, the government of Kalurahan Sumbermulyo devised strategies to use Dana Desa in 2022, not only to accommodate community aspirations resulting from the MusDes but also to fulfill the mandate of the Presidential Regulation.